Different aspects of severe asthma in real life: Role of Staphylococcus aureus enterotoxins and correlation to comorbidities and disease severity. Issue 1 (10th August 2022) - Caruso, Cristiano; Colantuono, Stefania; Ciasca, Gabriele; Basile, Umberto; Di Santo, Riccardo; Bagnasco, Diego; Passalacqua, Giovanni; Caminati, Marco; Michele, Schiappoli; Senna, Gianenrico; Heffler, Enrico; Canonica, G. Walter; et al.
Abstract: Background: Asthma, with several phenotypes and endotypes, is considered particularly suited for precision medicine. The identification of different non‐invasive biomarkers may facilitate diagnosis and treatment. Recently, Staphylococcus aureus and its enterotoxins (SE) have been found to have a role in inducing persistent type 2 airway inflammation in severe asthma, but also in such comorbidities as chronic rhinosinusitis with nasal polyposis (CRSwNP). Methods: The aim of this retrospective study was to evaluate the prevalence of SE‐IgE sensitization in a multicentric Italian cohort of severe asthmatic patients and correlate it with demographic and clinical characteristics. Results: A total of 249 patients were included in the analysis, out of which 25.3% were staphylococcal enterotoxin B (SEB)‐IgE positive. We found a meaningful association between SEB‐IgE and female gender, a positive association was also measured between CRS and CRSwNP. No significant association was found between SEB‐IgE sensitization and atopy, the occurrence of exacerbations and corticosteroid dosages. In the SEB‐IgE‐positive patient, blood eosinophil count does not appear to be correlated with the severity of the disease. Patients with SEB‐IgE sensitization are, on average, younger and with an earlier disease onset, thus confirming the possibility to consider SEB‐IgE sensitization as an independent risk factor for developing asthma. Conclusions: Our data confirm that the search for SE in the initial screening phase of these patients is helpful to better phenotype them, may predict the evolution of comorbidities and lead to a targeted therapeutic choice; in this point of view this represents a goal of precision medicine. Abstract : In patients diagnosed with severe asthma in Italy, the presence of enterotoxin sensitization for Staphylococcus appears to be an independent variable related to the development of comorbidities.Abbreviations: CI, confidence interval; CRS, chronic rhinosinusitis; CRSwNP, chronic rhinosinusitis with nasal polyps; IgE, immunoglobulin E; OR, odds ratio; SEB, staphylococcal enterotoxin B